2001
DOI: 10.3109/08977190109029114
|View full text |Cite
|
Sign up to set email alerts
|

Gdf-8 Propeptide Binds to GDF-8 and Antagonizes Biological Activity by Inhibiting GDF-8 Receptor Binding

Abstract: GDF-8 is a new member of the TGF-beta superfamily which appears to be a negative regulator of skeletal muscle mass. Factors which regulate the biological activity of GDF-8 have not yet been identified. However, the biological activities of TGF-beta superfamily members, TGF-beta1, -beta2 and -beta3, can be inhibited by noncovalent association with TGF-beta1, -beta2 and beta3 propeptides cleaved from the amino-termini of the TGF-beta precursor proteins. In contrast, the propeptides of other TGF-beta superfamily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
216
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(227 citation statements)
references
References 36 publications
9
216
0
2
Order By: Relevance
“…The ACVR2B͞Fc fusion protein was purified by using a protein A Sepharose column. Myostatin, GDF-11͞BMP-11, and activin activities were measured by using the pGL3-(CAGA) 12 -luciferase reporter assay in A204 rhabdomyosarcoma cells as described in ref. 12.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ACVR2B͞Fc fusion protein was purified by using a protein A Sepharose column. Myostatin, GDF-11͞BMP-11, and activin activities were measured by using the pGL3-(CAGA) 12 -luciferase reporter assay in A204 rhabdomyosarcoma cells as described in ref. 12.…”
Section: Methodsmentioning
confidence: 99%
“…Various myostatin-binding proteins have been identified that are capable of inhibiting myostatin activity in vitro (8,(11)(12)(13)(14)(15)(16). Two of these proteins, the JA16 neutralizing monoclonal antibody (Ab) directed against myostatin (8,15) and a mutant form of the myostatin propeptide resistant to members of the BMP-1͞tolloid family of metalloproteases (16), have been shown to be capable of increasing muscle mass by Ϸ25% when administered to wild-type (WT) mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another feature making myostatin potentially useful is its specificity. Like other TGF-b family members, the mature C-terminal protein binds to the N-terminal remnant of the original precursor molecule (LAP) resulting in a latent complex (Lee and McPherron, 2001;Thies et al, 2001;Yang et al, 2001). Myostatin then has to be released from this latent complex to be active.…”
Section: Rd Cell Growth Is Inhibited By Myostatinmentioning
confidence: 99%
“…Myostatin was expressed from a Chinese hamster ovary (CHO) cell line and purified similar to the method described in Thies et al 78 Crystallization of the RK35 and myostatin complex Chimeric RK35 was cleaved with immobilized papain for about 16 hours. Following cleavage, papain was removed using a disposable column.…”
Section: Cell Culture Expression and Purificationmentioning
confidence: 99%